Elan vital oder Das Auge des Eros - Gaßner, Hubertus,Kandinsky, Wassily,Klee, Paul,Arp, Hans,Miró, Joan,Calder, Alexander (Haus der Kunst, 1994)
Ausstellungskatalog
Werkverz. S. 547 - 566
Keywords: Ausstellungskatalog; Art; Abstract; Art; Modern